To solve the equation x² + 2x = 3, we first rearrange it into the form x² + 2x - 3 = 0.
Now, let's create a function graph of y = x² + 2x - 3 to visualize the solutions.
The graph will show that the equation crosses the x-axis at x = -3, x = 1, and x = 0.
Therefore, the solutions to the equation x² + 2x = 3 are x = -3 and x = 1.
Create a function graph to answer the question. Use the function graph to solve for the solutions to the equation x² + 2x = 3.
• x= 2,0
• x= -3,1
• no solution
• x= 0,1
1 answer